2015
DOI: 10.7567/apex.8.095501
|View full text |Cite
|
Sign up to set email alerts
|

Low-resistivitym-plane freestanding GaN substrate with very low point-defect concentrations grown by hydride vapor phase epitaxy on a GaN seed crystal synthesized by the ammonothermal method

Abstract: Please note that terms and conditions apply.Low-resistivity m-plane freestanding GaN substrate with very low point-defect concentrations grown by hydride vapor phase epitaxy on a GaN seed crystal synthesized by the ammonothermal method View the table of contents for this issue, or go to the journal homepage for more 2015 Appl. Phys. Express 8 095501An m-plane freestanding GaN substrate satisfying both low resistivity (ρ = 8.5 ' 10 %3 Ω&cm) and a low point-defect concentration, being applicable to vertically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
(79 reference statements)
1
17
0
Order By: Relevance
“…The sample M2, which was grown 27 by HVPE on a SCAAT seed, 28 exhibited the longest s 1 value. 29 These results confirm that principal limiting factor of s NR and thereby g int at room temperature is gross concentration of point defects (and defect complexes), which are incorporated with V Ga . From the results shown in Figs.…”
Section: A Origin Of Nonradiative Recombination Centers In N-type Gansupporting
confidence: 67%
See 1 more Smart Citation
“…The sample M2, which was grown 27 by HVPE on a SCAAT seed, 28 exhibited the longest s 1 value. 29 These results confirm that principal limiting factor of s NR and thereby g int at room temperature is gross concentration of point defects (and defect complexes), which are incorporated with V Ga . From the results shown in Figs.…”
Section: A Origin Of Nonradiative Recombination Centers In N-type Gansupporting
confidence: 67%
“…The longest s NR value among the samples measured under the same excitation conditions was 2.07 ns for M2. 29 A saturation of the decrease in s NR indicates that NRCs are fully activated, reflecting low gross N NRC . The decrease in g int at elevated temperatures is, therefore, due to the increase in s R .…”
Section: A Origin Of Nonradiative Recombination Centers In N-type Ganmentioning
confidence: 99%
“…[88] Positron methods have been widely applied to study vacancy defects in bulk nitride semiconductors, [34,78,80,[90][91][92][93][94][95] including crystals grown by the ammonothermal method. [44,79,96] Positrons implanted into a sample can get trapped in and localize at neutral and negative vacancies due to the missing positive ion core.…”
Section: Positron Annihilation Spectroscopymentioning
confidence: 99%
“…[20,30,31] Typical growth rates in the c-direction are in the range of a few hundred micrometers per day [22,26,32,33] and large arbitrary oriented substrates have been demonstrated. [26,[34][35][36] Ammonothermal GaN substrates have been used in homoepitaxy [35,37,38] and as substrates for InGaN LDs. [39] Although the crystalline quality of ammonothermal GaN is very high, recent studies have shown that the high concentration of impurities [22,40,41] and native point defects [42][43][44] in the as-grown material have a significant effect on the material properties.…”
Section: Progress Reportmentioning
confidence: 99%
“…The external quantum efficiency (EQE) in these devices is described by the product of internal quantum efficiency (IQE), current injection efficiency (CIE) and light extraction efficiency (LEE), among which, the IQE is an important factor reflecting the crystal quality of the active layers. The IQE values in IIInitride materials are usually estimated from temperature dependence of photoluminescence (PL) intensity [1]- [4]. In this method, the IQE at cryogenic temperature (below 10 K) is assumed as unity, and the IQE at room temperature (RT) is estimated as the ratio of the PL intensity at RT to that at low temperature.…”
Section: Introductionmentioning
confidence: 99%